Managerial competencies and experience in solving problems in an engineering company of movement: a case study - Suzete Suzana Rocha Pitombeira (2007)
The current study aimed to identify the degree of importance experience has as an element of competencies, in problem solving of management work. A case study was conducted descriptively throughout the research at a movement engineering company, located in the state of CearÃ, certified by ISO 9000/2000, which searches for quality in its strategic guidelines. Eight surveys were answered by the managers of various areas. The results of this data, along with the relevant theory, made it possible to check according to the ones researched that personal experience is necessary to the development of managers` basic and specific competencies, and these contribute to the solution of management problems. In practice, it is confirmed that competencies are made up by how workers see the job, build up and organize the knowledge and abilities in different competencies in the carrying out of their professional activities.